2015
DOI: 10.1007/s00374-015-1002-7
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere microbial community manipulated by 2 years of consecutive biofertilizer application associated with banana Fusarium wilt disease suppression

Abstract: In our previous work, applying biofertilizer containing Bacillus amyloliquefaciens strain NJN-6 to a banana orchard infected by a serious Fusarium wilt disease over two consecutive years effectively controlled this soil-borne disease. In this study, deep pyrosequencing of 16S ribosomal RNA (rRNA) genes and internal transcribed spacer (ITS) sequences was performed to investigate how the composition of rhizosphere microbial community responded to the application of biofertilizer (BIO), pig manure compost (PM), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
109
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(133 citation statements)
references
References 55 publications
(63 reference statements)
23
109
1
Order By: Relevance
“…However, fungal Shannon diversity was lower in BOF treatment than that in CK and CF treatments. These results were in agreement with the previous reports that BOF application decreased the soil fungal diversity in the rhizosphere of cucumber (Zhang et al, 2013), cotton (Luo et al, 2010), watermelon (Zhao et al, 2011) and banana (Shen et al, 2015a). The principal coordinate (PCoA) ( Figure 2 ) and permutational multivariate analysis (Supplementary Table S2) demonstrated that the fertilizer treatment was the more important factor than soil depth that influenced the soil microbial community composition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, fungal Shannon diversity was lower in BOF treatment than that in CK and CF treatments. These results were in agreement with the previous reports that BOF application decreased the soil fungal diversity in the rhizosphere of cucumber (Zhang et al, 2013), cotton (Luo et al, 2010), watermelon (Zhao et al, 2011) and banana (Shen et al, 2015a). The principal coordinate (PCoA) ( Figure 2 ) and permutational multivariate analysis (Supplementary Table S2) demonstrated that the fertilizer treatment was the more important factor than soil depth that influenced the soil microbial community composition.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the application of BOF increased the bacterial richness (Chao1) which was consistent with the results of Shen et al (2015a). However, fungal Shannon diversity was lower in BOF treatment than that in CK and CF treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Although Aspergillus did decline during fermentation, from a maximum of 91.48% on day 3 to 48.26% on day 15, Aspergillus oryzae remained a major genus throughout fermentation, indicating a high tolerance to the dry, high salt and high temperature conditions of the second step. Lichtheimia gradually declined in abundance during koji making, but increased during fermentation, from 12.26% on day 1 to 51.05% on day 15, suggesting this genus was adapted to the harsh environment, and indicating a key role in douchi fermentation [56], consistent with previous studies [60,61]. Burgess et al .…”
Section: Resultssupporting
confidence: 85%
“…Likewise, the genera Fusarium and Sordariales (no rank) dominated in IF-treated soils (Figure 2b). Our results indicating the prevalence of Fusarium in subtropical tea plantations are in agreement with the finding of Shen et al (2015), who reported that Fusarium was the dominant group in the rhizosphere from a different crop, i.e. banana, with quite different soil management practices.…”
Section: Effect Of Fertilization On Fungal Community Compositionsupporting
confidence: 82%
“…The genera unclassified Microascaceae, unclassified Ascomycota, and Agaricomycetes (no rank) are unique in IF-treated plots and rarely found in other two fertilizer treatments ( Figure 2b). These findings were broadly confirmed in arable soils and paddy soils at different sites, respectively (Shen et al, 2015;Chen et al, 2016), indicating that the combined applications of organic manures and chemical fertilizers resulted in the presence of a unique group of fungi in soils. This fungal community structure change may be caused by their responses to variations in soil organic C and N contents associated with integrated fertilization (Lazcano et al, 2013;Chen et al, 2016).…”
Section: Effect Of Fertilization On Fungal Community Compositionsupporting
confidence: 59%